Internalisasi Nilai Hukum Islam dalam Rancangan KUHP di Indonesia (Studi terhadap Tindak pidana perzinahan dalam KUHP dan RKUHP ) - Lisma Lisma (EKSPOSE, 2019)
AbstrakHukum pidana yang berlaku saat ini sejatinya sudah usang dan seharusnya diperbaharui untuk mengikuti perkembangan zaman, kendati demikian formulasi hukum pidana warisan kolonial hanya mementingkan aspek individual padahal hukum seyogianya memperhatikan aspek individual dan sosial. Hukum islam sebagai salah satu sistem hukum yang ada di dunia juga diakui dan berlaku di Indonesia bukan merupakan hal yang baru, berbagai aspek yang diatur dalam hukum islam sebenarnya mampu menjawab berbagai keresahan dalam praktik berhukum selama ini yang masih menggunakan hukum pidana warisan belanda. eksistensi hukum islam di Indonesia bukan hanya disebabkan oleh faktor sejarah melainkan masyarakat yang telah mendiami wilayah Nusantara telah memperaktikan nilai-nilai hukum islam sejak zaman kerajaan, sehingga masyarakat Indonesia yang beradab menolak segala bentuk perbuatan yang menyimpang dari norma agama, moral, sosial dan hukum. Namum praktik hukum islam pada masa penjajahan tidak dapat diberlakukan karena kaidah politik hukum menghendaki rezim politik mempengaruhi jenis hukum yang diberlakukan. Sejak berlakuknya hukum pidana kolonial hingga sekarang banyak menimbulkan persoalan-persoalan dalam masyarakat, seperti kumpul kebo, penistaan agama, perjudian dan minuman keras. Internalisasi hukum islam dalam pembaharuan hukum pidana sejalan dengan hukum kebiasaan dan hukum adat yang tidak memperbolehkan setiap perbuatan yang melanggar hukum kebiasaan dan hukum adat dalam suatu masyarakat seperti dalam budaya bugis siri’ yang tidak memperbolehkan membawa lari anak gadis orang begitupun di hukum adat kajang yang tidak memperbolehkan perempuan dan laki-laki berboncengan atau berdua-duan, di Aceh bahkan telah membuat aturan setingkat daerah tentang larangan seorang wanita dan laki-laki berdua-duan. Internalisasi nilai tersebut mengharuskan setiap formulasi hukum yang ingin dimasukan dalam RKUHP menggali saripati hukum islam yang berasal dari al-Qur’an, Sunnah dan Qiyas. Penelitian ini menggunakan metode deskriftif analitis dengan pendekatan yuridis normative yang mengkaji peraturan perundang-undangan yang berkaitan dengan persoalan tersebut dan dipadukan bahan-bahan hukum kepustakaan yang dapat menjelaskan fungsi hukum islam dalam memecahkan persolan hukum di Indonesia.AbstractThe current criminal law is in fact absoluete and should be renewed to keep pace with the times, not the formulation yet of the criminal law of the colonial inheritance is concerned only with the individual aspect whereas the law should pay attention to individual and social aspect. Islamic law as one of the existing legal system in the world is also recognized and applicable in Indonesia is not a new thing, the various aspects regulated in Islamic law is actually able to answer the various unrest in the practice of punishment so far that still use the dutch criminal law inheritance. The existence of islamic law in Indonesia is not only due to historical factors but the people who have inhabited the archipelago has been devoted to the values of Islamic law since the time of the kingdom, so that civilized Indonesian society reject all forms of acts deviating from religious, moral, social and legal norms. However, the practice of Islamic law in the colonial period can not be enforced because the political rule of law requires the political regime to influence the type of law imposed. Since the passage of colonial criminal law until now many cause problems in society, such as congregation kebo, blasphemy, gambling and liquor. The internalization of Islamic law in the renewal of the penal law is in line with customary law and customary law which does not allow any act that violates customary law and customary law in a society as in the siri 's bugis culture which does not permit the carrying of child girls as in customary kajang law allowing women and men to rally or to be together, even in Aceh have even made regional-level rules about the prohibition of a woman and a man on a budget. Internalization of these values requires that every formulation of law to be included in the draft penal code unearth the essence of Islamic law derived from the Qur'an, Sunnah and Qiyas. This study uses descriptive analytical method with normative juridical approach that examines the legislation relating to the issue and incorporated library literary materials that can explain the function of Islamic law in solving legal issues in Indonesia.The current criminal law is in fact absoluete and should be renewed to keep pace with the times, not the formulation yet of the criminal law of the colonial inheritance is concerned only with the individual aspect whereas the law should pay attention to individual and social aspect. Islamic law as one of the existing legal system in the world is also recognized and applicable in Indonesia is not a new thing, the various aspects regulated in Islamic law is actually able to answer the various unrest in the practice of punishment so far that still use the dutch criminal law inheritance. The existence of islamic law in Indonesia is not only due to historical factors but the people who have inhabited the archipelago has been devoted to the values of Islamic law since the time of the kingdom, so that civilized Indonesian society reject all forms of acts deviating from religious, moral, social and legal norms. However, the practice of Islamic law in the colonial period can not be enforced because the political rule of law requires the political regime to influence the type of law imposed. Since the passage of colonial criminal law until now many cause problems in society, such as congregation kebo, blasphemy, gambling and liquor. The internalization of Islamic law in the renewal of the penal law is in line with customary law and customary law which does not allow any act that violates customary law and customary law in a society as in the siri 's bugis culture which does not permit the carrying of child girls as in customary kajang law allowing women and men to rally or to be together, even in Aceh have even made regional-level rules about the prohibition of a woman and a man on a budget. Internalization of these values requires that every formulation of law to be included in the draft penal code unearth the essence of Islamic law derived from the Qur'an, Sunnah and Qiyas. This study uses descriptive analytical method with normative juridical approach that examines the legislation relating to the issue and incorporated library literary materials that can explain the function of Islamic law in solving legal issues in Indonesia.